Estoppel by Convention and Pre-Contractual Understandings: The Position and Practical Consequences - Bunting, Kristin (Victoria University of Wellington Law Review, 2011)
Recently, the House of Lords held in Chartbrook Ltd v Persimmon Homes Ltd that an understanding or common assumption reached by contracting parties in the course of their pre-contractual negotiations, including "an assumption that certain words will bear a certain meaning" can provide the basis for an estoppel by convention claim. This was reaffirmed by the New Zealand Supreme Court in Vector Gas Ltd v Bay of Plenty Energy Ltd. Both the House of Lords and the Supreme Court assumed that this was well established. Given that the issue was unsettled in England and with two divergent lines of authority in Australia, the House of Lords and Supreme Court should not have assumed this. In light of this development in the law, it is also argued that where the evidence proves that the parties established an understanding as to the meaning of a term in a proposed contract, then surely that is the meaning of that term, as a matter of interpretation. In addition, allowing consideration of pre-contractual negotiations to prove an estoppel by convention has undermined the rule that pre-contractual negotiations are inadmissible as an aid to interpretation of a contract.